2006
DOI: 10.1007/s10495-006-0292-5
|View full text |Cite
|
Sign up to set email alerts
|

Ischemic but not mechanical preconditioning attenuates ischemia/reperfusion induced myocardial apoptosis in anaesthetized rabbits: The role of Bcl-2 family proteins and ERK1/2

Abstract: The data provide further evidence that apoptosis and necrosis contribute independently to infarct size after ischemia and reperfusion. Inhibition of the myocardial apoptotic processes by IPC may involve modulation of the expression of anti-apoptotic proteins, Bcl-2 and Bcl-xL. ERK1/2 may be involved in the inhibition of both apoptosis and necrosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
31
0
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 54 publications
(35 citation statements)
references
References 40 publications
(57 reference statements)
3
31
0
1
Order By: Relevance
“…Some studies report associations between Bax expression and postischemic death, 59,62 and others report improved postischemic outcomes in the face of increased Bax, 63 or no relation between Bax expression and ischemic or hypoxic tolerance. 60,61,64 This raises the question of how shifts in Bax (or Bcl2/Bax) influence postischemic death, although one might speculate that reduced postischemic Bax and increased Bcl2 may serve to dampen or counter an age-related proapoptotic phenotype.…”
Section: Peart Et Almentioning
confidence: 99%
“…Some studies report associations between Bax expression and postischemic death, 59,62 and others report improved postischemic outcomes in the face of increased Bax, 63 or no relation between Bax expression and ischemic or hypoxic tolerance. 60,61,64 This raises the question of how shifts in Bax (or Bcl2/Bax) influence postischemic death, although one might speculate that reduced postischemic Bax and increased Bcl2 may serve to dampen or counter an age-related proapoptotic phenotype.…”
Section: Peart Et Almentioning
confidence: 99%
“…Ischemia preconditioning (IPC) is a phenomenon by which slight ischemia and reperfusion increase tissue tolerance to the subsequent lethal ischemia, partly by up-regulating VEGF expression (6) and attenuating ischemia-induced apoptosis (7). The uterine is hypoperfused in early and middle secretory phase (8), but it is hyperperfused in the late secretory phase (9).…”
mentioning
confidence: 99%
“…In addition, this method has been proven to be practical by evaluating postoperative sensorimotor functions and spinal cord histological changes. Accumulating evidence suggests that apoptosis triggered during the late phase of reperfusion plays a critical role in I/R-induced myocyte death, and inhibition of apoptosis, a highly regulated process, is a better target than necrosis which takes place during the very early phase of reperfusion [21][22][23][24]. Moreover, previous studies have shown that inhibiting I/R-induced myocardial apoptosis is beneficial to cardiac functional recovery [19,21].…”
Section: Discussionmentioning
confidence: 99%